Fear of intimacy in young adults from divorced families: a systematic review within attachment and family systems perspectives - Ridha Alisya Nur Hidayah; B. Primandini Yunanda Harumi (Universitas Ahmad Dahlan, 2026)
This literature review examines the development of research on fear of intimacy among young adults from divorced families within the framework of attachment theory and a family systems perspective. Although prior studies have investigated the impact of parental divorce on children’s psychological adjustment, there remains a limited understanding of the intrapersonal and relational mechanisms underlying the emergence of fear of intimacy in early adulthood. This review synthesizes findings from 18 peer-reviewed studies published between 2016 and 2025. The main themes identified include behavioral indicators of fear of intimacy (cognitive, emotional, and social), intrapersonal factors influencing fear of intimacy, and gender differences in its intensity and expression. The synthesis reveals that fear of intimacy is a multidimensional construct shaped by negative relational schemas, emotion regulation processes, insecure attachment patterns, and individuals’ capacity for self-acceptance and self-worth. This review highlights prevailing methodological trends dominated by correlational quantitative designs, theoretical contributions in integrating attachment theory and family systems perspectives, and practical implications for psychological interventions targeting young adults from divorced families. These findings provide a foundation for future research in the domains of interpersonal relationships and mental health in early adulthood.